2022
DOI: 10.5194/wcd-3-1-2022
|View full text |Cite
|
Sign up to set email alerts
|

Moisture origin, transport pathways, and driving processes of intense wintertime moisture transport into the Arctic

Abstract: Abstract. A substantial portion of the moisture transport into the Arctic occurs in episodic, high-amplitude events with strong impacts on the Arctic's climate system components such as sea ice. This study focuses on the origin of such moist-air intrusions during winter and examines the moisture sources, moisture transport pathways, and their linkage to the driving large-scale circulation patterns. For that purpose, 597 moist-air intrusions, defined as daily events of intense (exceeding the 90th anomaly percen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
(109 reference statements)
7
13
0
Order By: Relevance
“…The aerosol transport occurring higher up also connects to the findings from Papritz et al. (2022), who found that air subsiding from the mid‐troposphere into the boundary layer is as important an airstream as surface fluxes for the transport of moisture to the Arctic in wintertime. Using similar algorithms for heat transport as developed for ARs and p‐AARs, and cross comparing ARs, p‐AARs and heat transport events could allow the community to understand how moisture, aerosols, clouds, latent heat release and heat advection interact during these events, and quantify how these interactions impact the heat budget at high latitudes.…”
Section: Potential Applications Of P‐aarssupporting
confidence: 82%
“…The aerosol transport occurring higher up also connects to the findings from Papritz et al. (2022), who found that air subsiding from the mid‐troposphere into the boundary layer is as important an airstream as surface fluxes for the transport of moisture to the Arctic in wintertime. Using similar algorithms for heat transport as developed for ARs and p‐AARs, and cross comparing ARs, p‐AARs and heat transport events could allow the community to understand how moisture, aerosols, clouds, latent heat release and heat advection interact during these events, and quantify how these interactions impact the heat budget at high latitudes.…”
Section: Potential Applications Of P‐aarssupporting
confidence: 82%
“…The required wind fields are retrieved from ERA5 reanalysis on 137 model levels and its native spatiotemporal resolution. ERA5 wind fields have been used in many recent studies relying on trajectory analysis in the Arctic (e.g., Ali and Pithan, 2020;You et al, 2021;Papritz et al, 2022). Notably, during the WAI period in mid-April 2020, 4 radiosondes were launched daily at different locations upstream of RV Polarstern, and additional 7 radiosondes daily directly from RV Polarstern.…”
Section: Lagrangian Trajectoriesmentioning
confidence: 99%
“…Our trajectory analyses show that the corridor during 2020 is initially positioned over Greenland, and only later shifts to the Fram Strait/Iceland region (Section 3.2). In springtime, the North Atlantic WAI corridor is climatologically favored and has been reported to yield the most intense events (e.g., Mewes and Jacobi, 2019;Nygård et al, 2020;Papritz et al, 2022).…”
Section: Synoptic Overview and Circulation Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature changes are accompanied by reductions in sea ice area and thickness [3,4], increases in air humidity [5], changes in cloud cover [6][7][8], and changes in circulation regimes [3,9]. Changes in the characteristics of marine cold air outbreaks (MCAOs) over the Arctic Ocean are particularly indicative of circulation changes [5,10], which are critical for atmospheric interactions between the Arctic and midlatitudes [11]. In the Arctic, MCAOs occur when relatively cold and dry air masses from the sea ice regions move over the comparatively warmer ocean surface, triggering turbulent heat and moisture fluxes and promoting cloud formation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%